PENINGKATAN MUTU FISIOLOGIS DAN PERTUMBUHAN BENIH CABAI RAWIT (Capsicum frutescens) KEDALUARSA MELALUI TEKNIK INVIGORASI MENGGUNAKAN EKSTRAK JAGUNG MUDA - Ermawati, Netty; Ambar Agustiana, Linda; Santika, Putri (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2024)
One of the problems with companies engaged in seed production is that many seeds produced are not sold quickly and expire, resulting in a decrease in physiological quality. The purpose of this study was to determine the increase in the physiological quality and growth of expired cayenne pepper (Capsicum frutescens) seeds through the invigoration technique using young corn extract (Zea mays). The research was conducted using the Non-Factorial Completely Randomized Design (CRD) with the concentration of young corn extract (K) as the treatment factor. Data were analyzed using ANOVA and followed by DMRT level of 5%. The K factor consists of 5 levels; K0 (without soaking in young corn extract), K1 (20% of young corn extract), K2 (25% of young corn extract), K3 (30% of young corn extract), and K4 (35% of young corn extract ). The results showed that the use of young corn extract for invigoration of expired cayenne pepper seed had a significantly different effect on the parameters of growth synchrony and vigor index, and had a very significant effect on the parameters of germination power, maximum growth potential, and growth speed, compared to the control treatment. These results indicate that young corn extract is capable of acting as a bio-invigorator in improving the physiological quality of expired seeds